POSITIVE SOLUTIONS FOR SECOND ORDER INTEGRAL BOUNDARY VALUE PROBLEMS WITH SIGN-CHANGING NONLINEARITIES - Zou, Y. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
We prove the existence of positive solutions for the second order integral boundary value problem { arrayl u’’(t)+λ f(u(t))=0, t(0,1), 0.2cm u(0)=_0^1u(s)dα(s), u(1)=_0^1u(s)dβ(s), array . where fC(R,R) is sign-changing.